2015
DOI: 10.1080/15226514.2014.981247
|View full text |Cite
|
Sign up to set email alerts
|

Co-Planting Cd Contaminated Field Using HyperaccumulatorSolanum Nigrum L.Through Interplant with Low Accumulation Welsh Onion

Abstract: Monoculture and intercrop of hyperaccumulator Solanum nigrum L. with low accumulation Welsh onion Renbentieganchongwang were conducted. The results showed that the remove ratio of S. nigrum to Cd was about 7% in intercrop plot when top soil (0-20 cm) Cd concentration was 0.45-0.62 mg kg(-1), which did not significantly impact the yield of low accumulation Welsh onion compared to the monoculture. The consistency of remove ratio in practice and theory indicated the remediation of S. nigrum to Cd was significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…* Correlation is significant at p < 0.05 (two-tailed); * * correlation is significant at p < 0.01 (two-tailed). Japanese clover than when the respective crops were grown in monoculture [9,34]. In this study, the ability of heavy metal uptake of ryegrass roots was much higher than that of alfalfa.…”
Section: Effect Of the Intercropping Treatment On Heavy Metalmentioning
confidence: 54%
See 2 more Smart Citations
“…* Correlation is significant at p < 0.05 (two-tailed); * * correlation is significant at p < 0.01 (two-tailed). Japanese clover than when the respective crops were grown in monoculture [9,34]. In this study, the ability of heavy metal uptake of ryegrass roots was much higher than that of alfalfa.…”
Section: Effect Of the Intercropping Treatment On Heavy Metalmentioning
confidence: 54%
“…Ryegrass and alfalfa intercropping may form roots interlaced each other to provide a safe living environment for alfalfa to reduce the concentrations of heavy metals in alfalfa. Wang et al [9] found that the intercropping of Pteris vittata L. and faba bean can not only reduce the As content in the soil around the roots of Pteris vittata. L but also reduce the As content in the soil around the roots of faba bean.…”
Section: Effect Of the Intercropping Treatment On Heavy Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, As and Pb hyperaccumulator Pteris vittata (Chen et al, 2002a;Chen et al, 2002b;Ma et al, 2001;Wan et al, 2014) and Cd hyperaccumulator Sedum alfredii Hance (Long et al, 2009;Yang et al, 2004) were used in this type of soil. Intercropping system consisting of hyperaccumulators and cash crops with low HM accumulating abilities (Wang et al, 2015) were designed and established on the lowly contaminated soil to give the local farmers some income during remediation. The total area of the remediation project was 19.5 ha, distributed along the Huanjiang River (Fig.…”
Section: Efficiency Of Phytoremediationmentioning
confidence: 99%
“…In one study, researchers compared two species exposed to cadmium -Solanum torvum which does not accumulate significant amounts of cadmium in its tissues and Solanum nigrum which is identified as hyperaccumulator of Cd. Transcriptomic analyses identified a higher expression of multiple genes in S. nigrum which were involved in the transportation of metals and were not expressed in S. torvum [31]. Table 2.…”
Section: Transcriptomicmentioning
confidence: 99%